2024
DOI: 10.1101/2024.06.11.598543
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Direct computations of viscoelastic moduli of biomolecular condensates

Samuel R. Cohen,
Priya R. Banerjee,
Rohit V. Pappu

Abstract: In vitrofacsimiles of biomolecular condensates are formed by different types of intrinsically disordered proteins including prion-like low complexity domains (PLCDs). PLCD condensates are viscoelastic materials defined by time-dependent, sequence-specific complex shear moduli. Here, we show that viscoelastic moduli can be computed directly using a generalization of the Rouse model and information regarding intra- and inter-chain contacts that is extracted from equilibrium configurations of lattice-based Metrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 110 publications
0
1
0
Order By: Relevance
“…This weakening of pairwise associations enables networking that enables percolation within dense phases. Indeed, recent studies 49 have shown evidence for condensates being percolated network fluids 11,15,28,50 . Furthermore, the network structures directly explain the measured, sequence-specific viscoelastic moduli of different PLCD-based condensates 11 .…”
Section: Discussionmentioning
confidence: 99%
“…This weakening of pairwise associations enables networking that enables percolation within dense phases. Indeed, recent studies 49 have shown evidence for condensates being percolated network fluids 11,15,28,50 . Furthermore, the network structures directly explain the measured, sequence-specific viscoelastic moduli of different PLCD-based condensates 11 .…”
Section: Discussionmentioning
confidence: 99%